ANALISIS FAKTOR YANG MEMPENGARUHI PELAPORAN KEUANGAN PERUSAHAAN MELALUI INTERNET - Ardiastuti, Yuana; Widarno, Bambang; Harimurti, Fadjar (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study is to analyze the effect of firm size, profitability, liquidity, and new shares offering to internet financial reporting. The samples used in the study were 114 manufacture companies listed on the Indonesia Stock Exchange in 2018 with proportional stratified sampling method. The analytical method used is logistic regression. The result of this study indicate that the variable new shares offering significant and positive impact to internet financial reporting, while other variables firm size, profitability, and liquidity are not significant impact to internet financial reporting.